The research of friction pairs with tribo-recovery compositions with use the method of acoustic emission - Бабак, В.П.; Стадниченко, В.М.; Філоненко, С.Ф. (Proceedings of National Aviation University, 2004)
The results of research of the acoustic radiation of friction pairs both on the initial and tribo-recovery stages are brought. The main dependences of the alteration of acoustic emission, which correspond to the stage of the secondary wear-in are presented.